Price fluctuations of curly red Chilli and their effects on farmers' welfare in Pringsewu regency, Lampung: The influence of government policy and household income - Haryono, Dwi; Sabiela, Indah; Riantini, Maya; Tambunan, Varingan Prianando; Firdasari, Firdasari (Edelweiss Applied Science and Technology, 2025)
This research aims to analyze the income levels and overall welfare of households engaged in curly red chili farming in Pringsewu Regency, Lampung Province. The location was specifically selected because Pringsewu is a key center for curly red chili production in the area. Fifty-eight respondents were chosen through simple random sampling methods. Data was collected between October and November 2023. The analysis methods employed include assessments of household income and welfare levels. Information was gathered through interviews with curly red chili farmers using structured questionnaires. The study revealed that the average annual household income for these farmers is IDR 64,469,509.97. This income is primarily derived from core on-farm activities (65.03%), followed by supplementary on-farm sources (26.09%), off-farm sources (3.25%), and non-agricultural sources (5.63%). In terms of welfare, the majority of the farmers' households (70.69%) are considered to have a decent standard of living, while 29.31% are classified as having a moderately decent standard of living.